ANALISIS HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGA JUAL KERUPUK BAWANG DAN KERIPIK SINGKONG PADA HOME INDUSTRY â€œDUA BAWANGâ€ DI DESA SUCOLOR, KECAMATAN MAESAN, KABUPATEN BONDOWOSO - Abela, Isma; Puspita, Dini; Ahmadi, Riska Fitriya; Rhamadani, Vina Syahadatina; Widaninggar, Nanda (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This research was intended to find out the comparison between the calculation of the cost of goods sold for chips products in the "Dua Bawang" home industry using conventional/traditional methods and Full Costing methods. A qualitative approach with a case study design was the method of this research. Data collection was carried out using interview and documentation techniques. The data analysis presented in this research was comparative descriptive. The results of the research show that the cost of goods sold calculated based on Full Costing had different results from conventional/traditional method calculations with a better level of accuracy because Full Costing is a method of determining the cost of production which takes into account all cost elements into the cost of production which consists of raw material costs, direct labor costs and factory overhead costs, both variable and fixed. The management of home industry only records costs based on the money spent.